An update on: long-term outcomes of penile prostheses for the treatment of erectile dysfunction. (3rd April 2019) - Dick, Brian; Tsambarlis, Peter; Reddy, Amit; Hellstrom, Wayne JG
ABSTRACT: Introduction : Penile prosthesis placement is the gold standard for the treatment of erectile dysfunction (ED) refractory to medical therapy; however, limited data exist on the long-term outcomes of these devices. Areas covered : A PubMed search focused on long-term outcomes of penile prosthetics was performed. Studies with a follow-up of less than 5 years were excluded. Included studies were arranged chronologically by implant date to identify trends in device lifetime. Data were further scrutinized to separate device failure secondary to mechanical malfunction from device failure secondary to infection. Expert opinion : Limited data prevent accurate 15-year predictions for modern prosthetics. The 5- and 10-year overall survival of modern prosthetics is estimated to be 90.4% and 86.6%, respectively. Infection rates are estimated to be 1.5% and 1.8% at 8 and 10 years, respectively. While great strides have been made in device design, there is still potential for advancement in both infection rate reduction and mechanical improvement. The combination of increased collaboration between implanting urologists and engineers from prosthetic device companies and improved, prospectively collected data will usher prosthetic urology into its next era.